Contextualization of the Bejopai Pattern of the Kubin Dayak Tribe as a Contextual Discipleship Effort in West Kalimantan - Susanto Susanto; Sabda Budiman (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2021)
Dayak Kubin tribe has a culture that still survives to this day, namely Bejopai culture. Bejopai is an activity of the Dayak Kubin community that is generally done by working in the areas. Through the Bejopai culture conducted by the Dayak Kubin tribe in West Kalimantan, the author observes that contextual discipleship can be done. The problem formulation in this study is how the purpose of this writing is how the contextual discipleship approach in Dayak Kubin tribe through Bejopai culture in West Kalimantan? The aim is to present the contextual discipleship approach in the Dayak Kubin tribe through Bejopai Culture in West Kalimantan. The qualitative research method using qualitative methods is to make observations, interviews, or study documents. The locus of this study is in Sungai Bakah Village. Through the discussion results, it was found that contextual discipleship can be applied through persuasive communication approaches, patterns of working while telling stories, and discipleship to discipleship. The conclusion is that Bejopai culture can be used as a medium to do contextual discipleship that is quite effective in the Dayak Kubin tribe.